2001
DOI: 10.1073/pnas.191130798
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between growth arrest-DNA damage protein 34 and Src kinase Lyn negatively regulates genotoxic apoptosis

Abstract: Genotoxic stresses activate intracellular signaling molecules, which lead to growth arrest, DNA repair, and͞or apoptosis. Among these molecules are the growth arrest and DNA damage protein 34 (GADD34) and the Src-related protein tyrosine kinase Lyn. Here, we report that these two proteins physically and functionally interact to regulate DNA damage-induced apoptosis. Multiple isolates of GADD34 and the related murine protein MyD116 were identified as binding partners of Lyn in a yeast two-hybrid screen. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…Both PP1 and hSNF5/INI1 associate with GADD34 at its ICP34.5 homologous domain. Previously the Src kinase Lyn and proliferating cell nuclear antigen have both been shown to interact with GADD34 through this domain (51,52). Lyn binds to a SH3-like motif 50 amino acids apart from the PP1 and hSNF5/INI1 binding site (52).…”
Section: Hsnf5/ini1 In Gadd34 Functionmentioning
confidence: 99%
“…Both PP1 and hSNF5/INI1 associate with GADD34 at its ICP34.5 homologous domain. Previously the Src kinase Lyn and proliferating cell nuclear antigen have both been shown to interact with GADD34 through this domain (51,52). Lyn binds to a SH3-like motif 50 amino acids apart from the PP1 and hSNF5/INI1 binding site (52).…”
Section: Hsnf5/ini1 In Gadd34 Functionmentioning
confidence: 99%
“…Interestingly, while GADD34 overexpression augments radiation-induced apoptosis, HRX-fusion proteins, but not wild-type HRX proteins, inhibit GADD34-mediated apoptosis suggesting a possible mechanism of leukemogenesis through inhibition of DNA-damageinduced apoptosis by HRX-fusion proteins (Adler et al, 1999). Src kinase Lyn is activated by genotoxic stress, interacts with GADD34 and phosphorylates it, and this phosphorylation negatively regulates promotion of apoptosis by GADD34 following MMS treatment or ionizing radiation that might facilitate recovery following sublethal DNA damage (Grishin et al, 2001). A recent report has shown that GADD34 induces p53 phosphorylation and upregulation of p21 CIP-1/WAF-1/mda-6 , and these two factors might be important for mediating GADD34-induced growth inhibition .…”
Section: Introductionmentioning
confidence: 99%
“…GADD34, first identified in hamsters (Fornace et al, 1989), has been identified in human (Hollander et al, 1997), mouse (as Myd116) (Lord et al, 1990) and rat (Hollander et al, 2003) and exhibits high homology and similar domain structure across species. Induction of GADD34 has been shown to be associated with induction of apoptosis by diverse mechanisms and overexpression of GADD34 alone can markedly inhibit cell growth as a consequence of apoptosis (Hollander et al, 1997(Hollander et al, , 2001(Hollander et al, , 2003Adler et al, 1999;Grishin et al, 2001). The aminoterminal third of the GADD34 protein is involved in augmentation of apoptosis following ionizing radiation (Adler et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PP1, Snf5, Lyn kinase and HRXbinding domains have all been mapped to this region of Gadd34 (Figure 4), and interaction of Gadd34 with these proteins has been reported to be necessary for Gadd34-mediated growth suppression and apoptosis (Adler et al, 1999;Grishin et al, 2001;Novoa et al, 2001;Wu et al, 2002). In addition, HRX, G34BP, GaHSP40 and Translin all bind the carboxyl half of the protein, which includes the region missing in PEG-3 (Adler et al, 1999;Isobe, 1999, 2000;Hasegawa et al, 2000a, b).…”
Section: Discussionmentioning
confidence: 99%